Promoter and domain structures regulate FLA12 function during Arabidopsis secondary wall development - Ma, Yingxuan; Ratcliffe, Julian; Bacic, Antony; Johnson, Kim L. (Frontiers in Plant Science, 2023)
FASCICLIN-LIKE ARABINOGALACTAN-PROTEINs (FLAs) are a family of multi-domain glycoproteins present at the cell surface and walls of plants. Arabidopsis thaliana FLA12 and homologs in cotton, Populus, and flax have been shown to play important functions regulating secondary cell wall (SCW) development. FLA12 has been shown to have distinct roles from the closely related FLA11 that also functions during SCW development. The promoter and domain features of FLA12 that regulate functional specificity have not been well characterized. In this study, promoter swap experiments showed that FLA12 is differentially expressed in both stem and rosette leaves compared to FLA11. We then analyzed the role of post-translational modifications regulating FLA12 sub-cellular locations and found the glycosylphosphatidylinositol-anchor (GPI-anchor) was important for FLA12 location at the plasma membrane (PM)/cell wall interface. Domain swap experiments between FLA11 and FLA12 showed that the C-terminal arabinogalactan (AG) glycan motif acts as a key regulatory region differentiating FLA12 functions from FLA11. Understanding of FLA12 promoter and functional domains has provided new insights into the regulation of SCW development and functional specificity of FLAs for plant growth and development.